Empowerment Of Single Mothers as Family Heads in Tapos 1 Village, Tenjolaya District, Bogor Regency, West Java: A Strength-Based Approach - Fransisca, Angela (Cita konsultindo, 2025)
This study examines the empowerment of single mothers as family heads through a strength-based approach implemented by non-governmental organizations (NGOs) with the SOS Children’s Village program. A strengths-based approach is a collaborative process between service recipients and providers to determine outcomes by identifying and mobilizing an individual's inherent resources and assets. This approach views the risks or problems that clients have as enablers rather than obstacles. The role of the professional is not only to reduce risk; it is also to support the individual in managing risk. As single-mother households face socioeconomic vulnerabilities and societal stigma, NGO-led interventions that emphasize resilience and existing capabilities—rather than deficits—are critical for sustainable family strengthening. Using qualitative data from SOS Children’s Village participants, this research highlights how the family strengthening program leverages single mothers’ inherent strengths to improve household stability, financial independence, and child well-being. The results of the study demonstrate that a strengths-based approach, incorporating activities such as network development, stakeholder collaboration, provision of support facilities and initial business capital, and regeneration, can enhance the capacity of assisted families, particularly those led by female heads of households, to comprehend and implement effective parenting strategies. This approach can also facilitate increased income, enhanced access to government service programs, and reduce dependency on institutional aid. The study underscores the role of NGOs in filling gaps left by public welfare systems and proposes a framework for scaling strength-based interventions in similar contexts.